Flood crisis, ecological degradation, and hospital resilience in Sumatra: A One Health perspective - Budiman, Dicky; Chu, Cordia (Sociality: Journal of Public Health Service, 2025)
Flooding is Indonesia’s most recurrent hydrometeorological hazard, yet intervention-focused analyses that connect environmental degradation, infectious-disease risk, and health-service continuity through integrated One Health and Planetary Health lenses remain limited, especially for Sumatra, where rapid land-use change amplifies exposure and vulnerability. This study aims to analyze flooding in Sumatra as a multidimensional crisis by integrating One Health and Planetary Health perspectives while examining hospital resilience and crisis leadership during disaster response. A mixed-methods approach with descriptive-analytical analysis was applied using secondary data from disaster reports, health surveillance systems, scientific publications, and policy documents covering the period 2019–2024. The findings indicate that flood events in Sumatra increased from 126 cases in 2019 to 193 cases in 2024, affecting more than 380,000 people. The most frequently reported post-disaster diseases were diarrhea, leptospirosis, and acute respiratory infections. Substantial pressure on the healthcare system was evident, with approximately one-third to over half of hospitals experiencing disruptions in energy supply, water, and logistics, alongside patient visit increases of up to 45%, compounded by limitations in human resources. Moreover, variations in crisis leadership capacity across regions influenced the effectiveness of emergency responses. These findings suggest that flood preparedness in Sumatra should be implemented as an integrated health intervention package: One Health–based surveillance and risk communication, targeted WASH and vector/rodent control in high-risk rural communities, urban surge-capacity planning, and climate-resilient hospital measures (redundant power/water, supply-chain continuity, and incident-command training) aligned with global guidance.